2021
DOI: 10.1016/j.tranon.2021.101149
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effects of rigosertib in high-risk neuroblastoma

Abstract: Highlights Analysis of multiple tumor types reveal neuroblastoma sensitivity to rigosertib. Neuroblastoma 2D and 3D organoid models are sensitive to rigosertib. Rigosertib causes G2M cell cycle arrest rather than inhibition of Ras binding domains. Rigosertib prolongs survival of MYCN - amplified patient-derived xenograft tumors. Combination of rigosertib and vincristine is synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The 100 nm Rig concentration is consistent with Rig concentrations used in other studies; in fact, in all these works, Rig exhibited the same efficacy in reducing the viability of the cell lines evaluated, with effective concentrations starting approximately at 50–100 nM [ 6 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The 100 nm Rig concentration is consistent with Rig concentrations used in other studies; in fact, in all these works, Rig exhibited the same efficacy in reducing the viability of the cell lines evaluated, with effective concentrations starting approximately at 50–100 nM [ 6 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultssupporting
confidence: 86%
“…Moreover, Rig is capable of inducing senescence or cell death by apoptosis in several tumor cell lines, both in vitro and in vivo [ 4 , 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], increasing the production of ROS and altering the expression of numerous proteins involved in apoptosis (p53, BAX, MDM2) and in the formation of metastases (E-cadherins, matrix metalloproteinases 2 and 9) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroblastoma (NB) and Wilms tumor (WT) are two of the most common solid pediatric tumors, notorious for their rapid growth. We estimated growth rates from previously published data on untreated patientderived xenografts (PDX) derived from NB and WT 5,[19][20][21][22] . For comparison with adult tumors (i.e., slow growers) 23 , we also evaluated the uninhibited growth of several lung and breast cancer cell lines (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the efficacy and mechanism of rigosertib have been tested in rhabdomyosarcoma (RMS) and neuroblastoma (NBs) cell lines. Here, the authors showed that the main cytotoxic effect is due to an efficient cell arrest in mitosis, mainly by interfering with mitotic spindle assembly, which leads to cell death [46,47]. In fact, the authors have shown a similar behavior of rigosertib with respect to other Vinca alkaloids, although it is better tolerated.…”
Section: Rigosertib As a Tubulin Polymerization Destabilizermentioning
confidence: 94%